Toxicity of Carbon Nanotubes as Anti-Tumor Drug Carriers - Yan, Hongli (Int J Nanomedicine, 2019)
Nanoparticle drug formulations have enormous application prospects owing to achievement of targeted and sustained release drug delivery, improvement in drug solubility and reduction of adverse drug reactions. Recently, a variety of efficient drug nanometer carriers have been developed, among which carbon nanotubes (CNT) have been increasingly utilized in the field of cancer therapy. However, these nanotubes exert various toxic effects on the body due to their unique physical and chemical properties. CNT-induced toxicity is related to surface modification, degree of aggregation in vivo, and nanoparticle concentration. This review has focused on the potential toxic effects of CNTs utilized as anti-tumor drug carriers. The main modes by which CNTs enter target sites, the toxicity expressive types and the factors affecting toxicity are discussed.